MENINGKATKAN KEPUTUSAN PEMBELIAN MELALUI HARGA DAN PROMOSI PADA OUTLET KOPI KENANGAN DI KOTA PEKANBARU - Egim, Ash Shadiq; Fermayani, Riche; Yuliana, Liza; Janurdin, Hamdi (Bisnis-Net, 2024)
This research was conducted to determine the effect of price and promotion on consumer purchases at kenangan coffee shop in pekanbaru city riau. The analysis technique used in this research is quantitative with multiple linear regression analysis. This study used 97 respondents as a research sample by conducting a survey to consumers of Kenangan Coffee Connoisseurs in Pekanbaru City Riau. The results of the study prove that the variables of Price and Promotion, partially have no effect on consumer decisions. However, simultaneously there is a significant influence or a positive and significant effect on consumer decisions at the Kenangan coffee shop in Pekanbaru City, Riau.